Global drivers of timber carbon stock from income-based perspective - Wei, Ying; Yi, Meng; Yu, Yuxin; You, Yao; Zhang, Weidi; Li, Ruichao; Yu, Chang; Wang, Siyi (Frontiers in Environmental Science, 2023)
Timber and its products are key carriers of carbon stocks and can cause a hysteresis effect of carbon release in the carbon cycle of forest ecosystems. The literature regarding the cross-regional flow of timber carbon stock mainly pays attention to production- and consumption-based perspectives, which cannot reflect how the primary inputs drive timber carbon stock flow. The income-based perspective accounting can identify the influence of primary input suppliers and supplement research on timber carbon stock embodied in trade. The goal of this paper is to explore the cross-regional flow of global timber carbon stock and identify the critical countries from an income-based perspective using a multi-regional input-output model. It depicts the temporal and spatial characteristics of the income-based timber carbon stock and its flow in the main countries, reflecting the primary input suppliers' role. Furthermore, we also compared the different trends of production-based, consumption-based, and income-based timber carbon stocks and achieved a completed driven factor analysis from the entire timber supply chain. The results showed that the income-based timber carbon stock of the United States and China were among the top countries in imports and exports simultaneously. However, their export volumes were significantly larger, meaning that these countries have invested more primary resources in timber products. The timber carbon stock of the United States mainly flows into Canada and Brazil. In China, the largest flow went to Canada. Furthermore, the flow to the United States increased significantly. Moreover, comparing the three perspectives shows that the United States' primary inputs have a greater impact on the global timber production chain than their production- and consumption-based roles. Brazil and Russia, as main primary resource suppliers of timber carbon stock, are more important than as final consumers. The research can contribute to clarify the flow of forest resources embodied in global trade activities. Furthermore, it also provides a scientific basis to fairly account for carbon offset shares to achieve better the goal of forest resource protection agreed upon in COP26.